Electrochemical device and electronic device
By adding a specific proportion of acetate compounds, carbonate compounds and polynitrile compounds to the electrolyte of the electrochemical device, and adjusting the compaction density and channel structure of the negative electrode active material, the insufficient charging capacity and charging temperature of the electrochemical device are solved. The problem of increased results enables more efficient cycle performance and lower charging temperature rise.
Patent Information
- Application Number
- CN202411249697.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-25
- Publication Date
- 2024-12-17
AI Technical Summary
In the field of energy storage technology, the charging capacity of electrochemical devices is insufficient and the charging temperature rise is high, which affects their application efficiency and safety.
By optimizing the electrolyte composition, including adding additives such as acetate compounds, carbonate compounds, polynitrile compounds and fluoroethylene carbonate to the electrolyte, and controlling their mass percentage content range, combining appropriate negative electrode active material pressure The solid density and channel structure improve the circulation performance of the electrochemical device and reduce the charging temperature rise.
It significantly improves the circulation performance and charging capacity of the electrochemical device, reduces the charging temperature rise, extends the service life of the device and improves performance stability.
Smart Images

Figure BDA0005031903190000111 
Figure BDA0005031903190000121 
Figure BDA0005031903190000131
Abstract
Description
[0001] This application is a divisional application with application number 202111243754.6, application date October 25, 2021, and invention name “An electrochemical device and an electronic device”. Technical Field
[0002] The present application relates to the field of energy storage technology, and in particular to an electrochemical device and an electronic device. Background Art
[0003] Electrochemical devices, such as lithium-ion batteries, are widely used in wearable devices, smart phones, drones, laptops and other fields due to their advantages such as high operating voltage, high energy density, environmental friendliness, stable cycle and safety. With the development of modern information technology and the expansion of the application of electrochemical devices, the requirements for the charging capacity and charging temperature rise of electrochemical devices are becoming higher and higher.
[0004] In view of this, in the field of energy storage technology, improving the charging capacity of electrochemical devices and reducing their charging temperature rise have become urgent issues to be solved. Summary of the invention
[0005] The purpose of the present application is to provide an electrochemical device and an electronic device to reduce the charging temperature rise.
[0006] The first aspect of the present application provides an electrochemical device, which includes a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte includes an organic solvent, a lithium salt and an additive; the organic solvent includes an acetate compound and a carbonate compound, and the carbonate compound includes ethylene carbonate (EC) and propylene carbonate (PC), and based on the total mass of the electrolyte, the mass percentage A of the acetate compound is 4% to 50%, and the mass percentage B of the ethylene carbonate is 5% to 20%. Through in-depth research, the inventors found that the inclusion of the above-mentioned content of acetate compounds and carbonate compounds in the organic solvent can improve the cycle performance of the electrochemical device and reduce the charging temperature rise.
[0007] In some embodiments of the first aspect of the present application, the acetate compound includes at least one of methyl acetate, ethyl acetate, and propyl acetate.
[0008] In some embodiments of the first aspect of the present application, the electrolyte further comprises a polynitrile compound, and the polynitrile compound comprises at least two of succinonitrile, adiponitrile, 1,3,6-hexanetrinitrile, 1,2,3-tris(2-cyano)propane, ethylene glycol (bispropionitrile) ether and 1,4-dicyano-2-butene. By selecting the above polynitrile compounds, the cycle performance of the electrochemical device can be further improved and the charging temperature rise can be reduced.
[0009] In some embodiments of the first aspect of the present application, the mass percentage C of the polynitrile compound is 0.1% to 10%.
[0010] In some embodiments of the first aspect of the present application, the mass percentage C of the polynitrile compound and the mass percentage A of the acetate compound satisfy the relationship: 0.1≤C / A≤0.8. By controlling the value of C / A within the above range, the cycle performance of the electrochemical device can be improved.
[0011] In some embodiments of the first aspect of the present application, the additive comprises fluoroethylene carbonate (FEC), and the mass percentage D of the fluoroethylene carbonate and the mass percentage E of the propylene carbonate satisfy the relationship: 0.2≤D / E≤1.
[0012] In some embodiments of the first aspect of the present application, the mass percentage E of the propylene carbonate is 5% to 30% or the mass percentage D of the fluoroethylene carbonate is 0.1% to 15%. By regulating the content of fluoroethylene carbonate and the content of propylene carbonate within the above range, the cycle performance of the electrochemical device can be improved.
[0013] In some embodiments of the first aspect of the present application, the lithium salt is LiPF6, and the lithium salt content is 10% to 20% based on the total mass of the electrolyte.
[0014] In some embodiments of the first aspect of the present application, the compaction density of the negative electrode active material in the negative electrode is 1.40 g / cm 3 Up to 1.70g / cm 3 By controlling the compaction density of the negative electrode active material within the above range, the cycle performance of the electrochemical device can be further improved and the charging temperature rise can be reduced.
[0015] In some embodiments of the first aspect of the present application, the negative electrode comprises pores, and the pores satisfy at least one of the following conditions: (a) 20 μm to 100 μm, (b) pore depth ranges from 5 μm to 50 μm, (c) the number of pores per unit area is 0.5 / mm 2 Up to 100 pieces / mm 2 By regulating the pore diameter, pore depth, and number of pores per unit area of the negative electrode pores within the above ranges, the cycle performance of the electrochemical device can be further improved and the charging temperature rise can be reduced.
[0016] A second aspect of the present application provides an electronic device, which includes the electrochemical device provided in the first aspect of the present application.
[0017] The electrochemical device and electronic device of the present application can improve the kinetic characteristics of the electrochemical device, enhance the charging capacity, and reduce the charging temperature rise by optimizing the solvent content and type in the electrolyte. The charging capacity can be further enhanced and the charging temperature rise can be reduced by adding appropriate additives to the electrolyte.
[0018] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field based on the present application belong to the scope of protection of the present application.
[0020] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of electrochemical devices to explain this application, but the electrochemical devices of this application are not limited to lithium-ion batteries. Those skilled in the art should understand that the following description is only for illustrative purposes and does not limit the scope of protection of this application.
[0021] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0022] In a first aspect, the present application provides an electrochemical device, comprising a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte comprises an organic solvent, a lithium salt and an additive; the organic solvent comprises an acetate compound and a carbonate compound, the carbonate compound comprises ethylene carbonate and propylene carbonate, and based on the total mass of the electrolyte, the mass percentage A of the acetate compound is 4% to 50%, for example, the mass percentage A of the acetate compound can be 4%, 10%, 12%, 20%, 28%, 36%, 50% or any range therebetween; the mass percentage B of the ethylene carbonate is 5% to 20%, for example, the content B of the ethylene carbonate can be 5%, 8%, 11%, 14%, 17%, 20% or any range therebetween.
[0023] The inventors of the present application have found through research that by adjusting the organic solvent to include acetate compounds and carbonate compounds, and controlling the content of acetate compounds and ethylene carbonate within the above range, it is helpful to improve the lithium salt dissociation rate and the stability of the solid electrolyte interface (SEI) film during the cycle of the electrochemical device. Thereby improving the kinetic performance of the electrochemical device, improving the cycle performance, and reducing the charging temperature rise.
[0024] In some embodiments of the present application, the acetate compound includes at least one of methyl acetate, ethyl acetate, and propyl acetate. Without being limited to any theory, the inventors of the present application have found that since the above acetate compounds all have a relatively low viscosity, they are beneficial for improving the transmission of lithium ions during charging, reducing the transmission impedance, and thus reducing the charging temperature rise of the electrochemical device.
[0025] In some embodiments of the present application, the electrolyte further comprises a polynitrile compound, the polynitrile compound comprising at least two of succinonitrile (SN), adiponitrile (AND), 1,3,6-hexanetrinitrile (HTCN), 1,2,3-tris(2-cyano)propane (TCEP), ethylene glycol (bispropionitrile) ether (DENE) and 1,4-dicyano-2-butene (HEDN). Without being limited to any theory, the inventors of the present application have found that when at least two combinations of the above polynitrile compounds are selected, it is beneficial to improve the stability of the SEI film during the cycle of the electrochemical device, thereby improving the cycle performance of the electrochemical device and reducing the charging temperature rise.
[0026] In some embodiments of the first aspect of the present application, the mass percentage C of the polynitrile compound is 0.1% to 10%. For example, the mass percentage C of the polynitrile compound can be 0.1%, 1%, 2%, 4%, 6%, 8%, 10% or any range therebetween.
[0027] In some embodiments of the first aspect of the present application, the content C of the polynitrile compound and the content A of the acetate compound satisfy the relationship: 0.1≤C / A≤0.8. For example, the value of C / A can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or any range therebetween. The inventors of the present application have found that when the value of C / A is too low, for example, lower than 0.1, the cycle performance and charging temperature rise of the electrochemical device are not significantly improved; when the value of C / A is too high, for example, higher than 0.8, the content of the polynitrile compound is too high or the content of the acetate is too low, the viscosity of the electrolyte increases, and the polarization of the cycle process is large, which will affect the charging temperature rise and cycle performance of the electrochemical device. By regulating the value of C / A within the above range, it is beneficial to further improve the cycle performance of the electrochemical device and reduce the charging temperature rise.
[0028] In some embodiments of the present application, the additive comprises fluoroethylene carbonate (FEC), the mass percentage of the fluoroethylene carbonate is D, and the content D of the fluoroethylene carbonate and the content E of the propylene carbonate satisfy the relationship: 0.2≤D / E≤1. For example, the value of D / E can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1 or any range therebetween. Without being limited to any theory, the inventors of the present application have found that when the ratio of the content of FEC to the content of propylene carbonate is too low, for example, when D / E is less than 0.2, due to the large viscosity of the solvent, the internal resistance of the lithium-ion battery is increased, the charging temperature rise is increased, and at the same time, the anode protection is insufficient, and the cycle performance is poor; when the content of FEC to the content of propylene carbonate is too high, for example, when D / E is greater than 1, the lithium salt is insufficiently dissociated, the temperature rise increases, and at the same time, the FEC content is too high, the high temperature stability is poor, and the cycle becomes poor. By regulating the content ratio of fluoroethylene carbonate to propylene carbonate within the above range, it is beneficial to improve the cycle performance of the electrochemical device and reduce the charging temperature rise.
[0029] In some embodiments of the present application, the mass percentage E of the propylene carbonate is 5% to 30% or the mass percentage D of the fluoroethylene carbonate is 0.1% to 15%, for example, E can be 5%, 10%, 12%, 14%, 16%, 18%, 20%, 30% or any range therebetween, and D can be 0.1%, 1%, 3%, 5%, 7%, 9%, 11%, 15% or any range therebetween.
[0030] In some embodiments of the present application, the lithium salt is LiPF6, and the lithium salt content is 10% to 20% based on the total mass of the electrolyte. For example, the content of the lithium salt can be 10%, 12%, 14%, 16%, 18%, 20% or any range therebetween. Without being limited to any theory, the inventors of the present application have found that by regulating the lithium salt content within the above range, during the cycle of the electrochemical device, it is beneficial to improve the conductivity, thereby improving the cycle performance of the electrochemical device.
[0031] In the present application, the electrolyte may also include other non-aqueous solvents. The present application has no particular restrictions on other non-aqueous solvents, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of carboxylic acid ester compounds, ether compounds or other organic solvents. The above-mentioned carboxylic acid ester compounds may include but are not limited to at least one of methyl formate, ethyl formate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valerolactone or caprolactone. The above-mentioned ether compounds may include but are not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, trimethyl phosphate, triethyl phosphate, and trioctyl phosphate. Based on the total mass of the electrolyte, the total content of the above-mentioned other non-aqueous solvents is 5% to 60%, for example, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or any range therebetween.
[0032] In the present application, the electrolyte may further include other additives. There is no particular limitation on other additives in the present application as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of lithium tetrafluoroborate (LiBF4), vinyl sulfate (DTD), vinyl carbonate (VC), vinyl sulfite (PS) or lithium dioxalate borate (LiBOB).
[0033] In some embodiments of the present application, it comprises a negative electrode, wherein the compaction density of the negative electrode active material in the negative electrode is 1.40 g / cm 3 Up to 1.70g / cm 3 For example, the compaction density of the negative electrode active material can be 1.40 g / cm 3 , 1.45g / cm 3 , 1.50g / cm 3 , 1.55g / cm 3 , 1.60g / cm 3 , 1.65g / cm 3 , 1.70g / cm 3 Without being limited to any theory, the inventors of the present application have found that when the compaction density of the negative electrode active material is too low, for example, less than 1.40 g / cm 3 , the contact between negative electrode materials in electrochemical devices is poor, electronic conduction and ion conduction are blocked, charging temperature rises and cycle performance is poor; when the compaction density of negative electrode active materials is too high, for example, higher than 1.70g / cm 3, the negative electrode is prone to overvoltage, poor charging capacity, high charging temperature and poor cycle performance, and there is also a risk of material particles breaking due to overvoltage. By regulating the compaction density of the negative electrode active material within the above range, the cycle performance of the electrochemical device can be improved and its charging temperature rise can be reduced.
[0034] In some embodiments of the present application, the negative electrode material in the negative electrode includes at least one of carbon material, silicon, silicon-oxygen material, and silicon-carbon material, and the carbon material includes at least one of natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, and soft carbon.
[0035] In some embodiments of the present application, the negative electrode comprises pores, and the pores satisfy at least one of the following conditions: (a) the pore diameter of the pores is 20 μm to 100 μm, for example, the pore diameter can be 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm or any range therebetween; (b) the pore depth range is 5 μm to 50 μm, for example, the pore depth can be 5 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm or any range therebetween; (c) the number of pores per unit area is 0.5 pores / mm 2 Up to 100 pieces / mm 2 For example, the number of holes per unit area can be 0.5 / mm 2 , 1 piece / mm 2 , 10 / mm 2 , 20 pieces / mm 2 , 30 pieces / mm 2 , 40 pieces / mm 2 , 50 pieces / mm 2 , 60 pieces / mm 2 , 70 pieces / mm 2 , 80 pieces / mm 2 , 90 pieces / mm 2 , 100 pieces / mm 2 Or any range therebetween. Without being limited to any theory, the inventors of the present application have found that by controlling the intensity of infrared laser, drilling holes on the surface of the negative electrode plate, and controlling the hole diameter, hole depth, and number of holes per unit area within the above range, it is beneficial to the infiltration of electrolyte between materials and the transmission of lithium ions, reducing the transmission impedance, thereby improving the cycle performance of the electrochemical device and reducing the charging temperature rise.
[0036] There is no particular limitation on the positive electrode sheet in the present application, as long as the purpose of the present application can be achieved. The positive electrode sheet generally comprises a positive current collector and a positive active material. The above-mentioned positive current collector is not particularly limited, and may be any positive current collector known in the art, such as copper foil, aluminum foil, aluminum alloy foil, and composite current collector. The above-mentioned positive active material is not particularly limited, and may be any positive active material of the prior art, for example, it may include at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, or lithium iron manganese phosphate.
[0037] In the present application, the thickness of the positive electrode current collector and the positive electrode active material is not particularly limited as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 8 μm to 12 μm, and the thickness of the positive electrode active material is 30 μm to 120 μm.
[0038] In the present application, the positive electrode active material layer may also include a conductive agent, and the present application has no particular restrictions on the conductive agent, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, Ketjen black, graphene, metal materials or conductive polymers. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers, and specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole.
[0039] In the present application, the positive electrode active material layer may also include a binder. There is no particular limitation on the binder as long as the purpose of the present application can be achieved. For example, it may include but is not limited to polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin, nylon, etc.
[0040] Optionally, the positive electrode may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The present application has no particular limitation on the composition of the conductive layer, which may be a commonly used conductive layer in the art, for example, including but not limited to the above conductive agent and the above binder.
[0041] There is no particular restriction on the negative electrode current collector in the present application, as long as the purpose of the present application can be achieved, and materials such as metal foil or porous metal plate can be used, such as foil or porous plate of metals such as copper, nickel, titanium or iron or their alloys, such as copper foil. The negative electrode active material layer includes a negative electrode active material, a conductive agent, a binder and a thickener. The binder can be at least one of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), water-based acrylic resin or carboxymethyl cellulose (CMC); the thickener can be sodium carboxymethyl cellulose (CMC). In the present application, there is no particular restriction on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4μm to 12μm.
[0042] In the present application, the negative electrode material layer may further include a conductive agent, and the present application has no particular limitation on the conductive agent, as long as the purpose of the present application can be achieved.
[0043] In the present application, the negative electrode material layer may further include a binder, and the present application has no particular limitation on the binder, as long as the purpose of the present application can be achieved.
[0044] Optionally, the negative electrode may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular limitation on the composition of the conductive layer, which may be a conductive layer commonly used in the art.
[0045] There is no particular limitation on the isolation membrane in the present application, as long as the purpose of the present application can be achieved. The isolation membrane may include a substrate layer and a surface treatment layer. The present application has no particular limitation on the substrate layer, for example, it may include but is not limited to polyethylene (PE), polypropylene (PP), polytetrafluoroethylene-based polyolefin (PO)-based diaphragms, polyester films (such as polyethylene terephthalate (PET) films), cellulose films, polyimide films (PI), polyamide films (PA), spandex, aramid films, woven films, non-woven films (non-woven fabrics), microporous films, composite films, diaphragm paper, rolled films or spinning films. At least one of them is preferably PP. The isolation membrane of the present application may have a porous structure, and the size of the pore size is not particularly limited, as long as the purpose of the present application can be achieved. For example, the size of the pore size can be 0.01μm to 1μm. In the present application, the thickness of the isolation membrane is not particularly limited, as long as the purpose of the present application can be achieved. For example, the thickness can be 5μm to 500μm.
[0046] In the present application, a surface treatment layer may also be provided on at least one surface of the substrate layer. The present application has no particular restrictions on the surface treatment layer, which may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. The inorganic layer may include, but is not limited to, inorganic particles and an inorganic layer binder. The present application has no particular restrictions on inorganic particles, for example, may include but is not limited to at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the inorganic layer binder, for example, may include but is not limited to at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The polymer layer contains polymers, and the polymer material may include but is not limited to at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).
[0047] The electrochemical device of the present application is not particularly limited, and may include any device that undergoes an electrochemical reaction. In some embodiments, the electrochemical device may include, but is not limited to, a lithium-ion battery.
[0048] The preparation process of the electrochemical device is well known to those skilled in the art, and the present application has no particular limitation. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a wound structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain an electrochemical device; or stacking the positive electrode, the separator and the negative electrode in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the packaging bag as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.
[0049] The second aspect of the present application provides an electronic device, comprising the electrochemical device in any of the aforementioned embodiments of the present application. The electrochemical device provided by the present application has good cycle performance and low charging temperature rise, so that the electronic device provided by the present application has a long service life and good performance.
[0050] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. For example, the display device includes but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0051] Test methods and equipment:
[0052] Lithium deposition test:
[0053] The battery was charged at 3C to 4.45V at 25℃, then charged at constant voltage to 0.05C at 4.45V, and then discharged at constant current of 1.0C to 3.0V, and cycled for 10 cycles. The battery was disassembled to observe the degree of lithium deposition. No lithium deposition or lithium deposition area <2% is called no lithium deposition; lithium deposition area between 2% and 20% is called slight lithium deposition; lithium deposition area >20% is called severe lithium deposition.
[0054] Temperature rise test:
[0055] At the test temperature of 25℃, the battery was charged to 4.45V at a constant current of 0.5C, then charged to 0.05C at a constant voltage, and left to stand for 60min. The lithium-ion battery was then discharged to 3V at a constant current of 0.5C, and left to stand for 60min. The lithium-ion battery was charged to 4.45V at a constant current of 6C, and then charged to 0.05C at a constant voltage. The temperature during the high-current charging process was monitored, and the test temperature of 25℃ was subtracted to obtain the 6C charging temperature rise.
[0056] High temperature cycle test:
[0057] The battery was placed in a 45°C constant temperature box, charged to 4.45V at a constant current of 1.5C, charged to 0.05C at a constant voltage of 4.45V, and then discharged to 3.0V at a constant current of 1.0C. This was a charge and discharge cycle. The charge and discharge test was performed 800 times in the above manner to monitor the capacity retention rate. The 45°C cycle capacity retention rate = (discharge capacity of the 800th cycle / initial discharge capacity) × 100%.
[0058] Test of component content in electrolyte:
[0059] The battery cell was discharged and centrifuged, and the liquid obtained after centrifugation was subjected to GC-MS test; the percentage of each component (acetate, EC, PC, additives) was detected.
[0060] Compaction density test of negative electrode active material:
[0061] The compaction density of the negative electrode active material is measured by the following method:
[0062] Take the negative double-sided electrode sheet and make it into an area of 1540.25mm 2 Take 20 small discs for weighing and thickness measurement, the compaction density of negative electrode active material = (weight of small disc - weight of substrate) / (1540.25 × (double-sided thickness of small disc - thickness of substrate)) × 1000, and the test average value is the negative electrode compaction in the embodiment.
[0063] Weight and thickness of substrate (copper foil): obtained by weighing and measuring the area without active material;
[0064] Weight of small disc and substrate: Unit (mg)
[0065] Double-sided thickness of the wafer and substrate thickness: unit (μm).
[0066] Pore feature test on negative electrode sheet:
[0067] The pore characteristic data (pore diameter, pore depth, and number of pores per unit area) on the negative electrode sheet were obtained through tunnel scanning microscopy testing.
[0068] Example 1
[0069] (1) Preparation of negative electrode sheet: Mix the negative electrode active materials artificial graphite, styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) in a mass ratio of 97.4:1.2:1.4, then add deionized water as a solvent, prepare a slurry with a solid content of 70wt%, and stir evenly. The slurry is evenly coated on one surface of a copper foil with a thickness of 8μm, dried at 110°C, and cold pressed to obtain a negative electrode sheet with a single-sided negative electrode active material layer coated with a negative electrode active material layer with a thickness of 150μm, and then repeat the above coating steps on the other surface of the negative electrode sheet to obtain a negative electrode sheet with a double-sided negative electrode active material layer coated. Cut the negative electrode sheet into a specification of (74mm×867mm) and weld the tabs for standby use.
[0070] (2) Preparation of positive electrode sheet: The positive electrode active material lithium cobalt oxide (LiCoO2), the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96:2:2, and N-methylpyrrolidone (NMP) is added as a solvent. The system is stirred under the action of a vacuum mixer until the system becomes a uniform positive electrode slurry with a solid content of 75wt%. The positive electrode slurry is evenly coated on a positive electrode current collector aluminum foil with a thickness of 12μm, dried at 85°C, and cold pressed to obtain a positive electrode sheet with a positive electrode active material layer thickness of 100μm, and then the above steps are repeated on the other surface of the positive electrode sheet to obtain a positive electrode sheet with a positive electrode active material layer coated on both sides. The positive electrode sheet is cut into a specification of 74mm×867mm and welded to the pole ears for standby use.
[0071] (3) Preparation of electrolyte: In an argon atmosphere glove box with a water content of <10ppm, ethylene carbonate (EC), propylene carbonate (PC), ethyl acetate (EA) and ethyl propionate (EP) are mixed evenly, and then the fully dried lithium salt LiPF6 is dissolved in the above non-aqueous solvent, and the additive fluoroethylene carbonate is added to finally prepare a basic electrolyte. Among them, the mass percentage of lithium salt is 10%, the contents of EC, PC, EA, and FEC are 10%, 15%, 4%, and 7.5% respectively, and the rest of the electrolyte is ethyl propionate, wherein the ratio of the content of fluoroethylene carbonate to the content of ethylene carbonate is 0.5.
[0072] (4) Isolation membrane: PE porous polymer film is used as the isolation membrane.
[0073] (5) Preparation of lithium-ion batteries: stack the positive electrode sheet, separator, and negative electrode sheet in order, with the separator placed between the positive and negative electrodes to serve as an isolation, and then wind them to obtain a bare cell; place the bare cell in an outer packaging foil, inject the prepared electrolyte into the dried cell, and complete the preparation of the lithium-ion battery after vacuum packaging, standing, forming, shaping, and other processes.
[0074] In Examples 2 to 21, the preparation steps of <Preparation of negative electrode sheet>, <Preparation of positive electrode sheet>, <Preparation of electrolyte>, <Preparation of diaphragm> and <Preparation of lithium-ion battery> are the same as those in Example 1, and the changes in relevant preparation parameters and performance parameters are shown in Table 1.
[0075] In Examples 22 to 43 and 46, except for adding a polynitrile compound to the electrolyte of Example 3 and adjusting the type and content of the polynitrile compound, the total content of the polynitrile compound and the ratio of the content of the polynitrile compound to the content of the acetate compound as shown in Table 2, the rest is the same as Example 3.
[0076] In Example 44, except for adding a polynitrile compound to the electrolyte of Example 2, and adjusting the type and content of the polynitrile compound, the total content of the polynitrile compound, and the ratio of the content of the polynitrile compound to the content of the acetate compound as shown in Table 2, the rest is the same as Example 2.
[0077] In Example 45, except for adding a polynitrile compound to the electrolyte of Example 10, adjusting the type and content of the polynitrile compound, the total content of the polynitrile compound and the ratio of the content of the polynitrile compound to the content of the acetate compound as shown in Table 2, the rest is the same as Example 10.
[0078] In Examples 47 to 55, except for adjusting the compaction density of the negative electrode active material, the pore diameter, pore depth and the number of pores per unit area on the negative electrode sheet as shown in Table 3 based on the electrolyte of Examples 23 to 31, the rest is the same as Examples 23 to 31.
[0079] In Comparative Examples 1 to 7, the preparation steps of <Preparation of Negative Electrode Plate>, <Preparation of Positive Electrode Plate>, <Preparation of Electrolyte>, <Preparation of Diaphragm> and <Preparation of Lithium-ion Battery> are the same as those in Example 1, and the changes in relevant preparation parameters and performance are shown in Table 1.
[0080] Table 1
[0081]
[0082]
[0083] In Table 1, “ / ” indicates that there is no corresponding preparation parameter.
[0084] Table 2
[0085]
[0086] Table 3
[0087]
[0088] It can be seen from Examples 1 to 10 and Comparative Examples 1 to 3 that with the increase of ethyl acetate content, lithium precipitation and charging temperature rise are improved, but the cycle performance is reduced when the ethyl acetate content is high; when no acetate compound is contained, lithium precipitation worsens, the cycle performance deteriorates, and the charging temperature rise is significantly increased; when the acetate compound content is too low, lithium precipitation is serious, the cycle deteriorates, and the charging temperature rise increases; when the acetate compound content is too high, the cycle cannot be cycled, and gas production dive occurs.
[0089] It can be seen from Example 3, Example 11 to Example 13, Comparative Example 4 and Comparative Example 5 that when the EC content is low, due to the dissociation of the lithium salt, the interface stability is improved, the kinetic performance is improved, and thus the cycle performance is improved; when the EC content is too high, the viscosity increases and the stability also deteriorates; however, when the EC content is too low, the cycle performance is poor and lithium deposition is severe; when the EC content is too high, the cycle performance is poor and lithium deposition is severe.
[0090] It can be seen from Example 3, Example 14 and Example 15, Comparative Example 6 and Comparative Example 7 that when the FEC / PC value is within the range of this application, the lithium deposition and charging temperature rise are improved when it is lower. When FEC / PC is too small, the cycle performance is reduced. When FEC / PC is too high, lithium deposition is serious.
[0091] It can be seen from Example 2, Example 3, Example 10 and Example 22 to Example 46 that with the addition of the polynitrile compound, the stability of the SEI film is further improved during the cycle process, thereby improving the cycle performance.
[0092] It can be seen from Example 40 and Example 47 to Example 49 that as the pore size of the channel on the negative electrode plate increases, the lithium deposition situation and the charging temperature rise are improved.
[0093] The above description is only a preferred embodiment of the present application and is not intended to limit the protection scope of the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application are included in the protection scope of the present application.
Claims
1. An electrochemical device comprising a positive electrode, a negative electrode and an electrolyte, wherein: The electrolyte comprises an organic solvent, a lithium salt and an additive; the organic solvent comprises an acetate compound and a carbonate compound, the carbonate compound comprises ethylene carbonate and propylene carbonate, and based on the total mass of the electrolyte, the mass percentage B of the ethylene carbonate is 10% to 20%, and the mass percentage E of the propylene carbonate is 10% to 20%.
2. The electrochemical device according to claim 1, wherein: The acetate compound includes at least one of methyl acetate, ethyl acetate and propyl acetate.
3. The electrochemical device according to claim 1, wherein The electrolyte further comprises a polynitrile compound, wherein the polynitrile compound comprises at least two of succinonitrile, adiponitrile, 1,3,6-hexanetrinitrile, 1,2,3-tris(2-cyano)propane, ethylene glycol (bispropionitrile) ether and 1,4-dicyano-2-butene.
4. The electrochemical device according to claim 3, wherein: The mass percentage C of the polynitrile compound is 0.1% to 10%.
5. The electrochemical device according to claim 3, wherein: The mass percentage content C of the polynitrile compound and the mass percentage content A of the acetate compound satisfy the relationship: 0.1≤C / A≤0.
8.
6. The electrochemical device according to claim 1, wherein The additive comprises fluoroethylene carbonate, and the mass percentage D of the fluoroethylene carbonate and the mass percentage E of the propylene carbonate satisfy the relationship: 0.2≤D / E≤1.
7. The electrochemical device according to claim 6, wherein: The mass percentage D of the fluoroethylene carbonate is 0.1% to 15%.
8. The electrochemical device according to claim 1, wherein The compaction density of the negative electrode active material in the negative electrode is 1.40 g / cm 3 Up to 1.70g / cm 3 .
9. The electrochemical device according to claim 1, wherein: The negative electrode comprises pores, wherein the pores satisfy at least one of the following conditions: (a) a pore diameter of 20 μm to 100 μm; (b) a pore depth of 5 μm to 50 μm; (c) a pore number per unit area of 0.5 pores / mm 2 Up to 100 pieces / mm 2 .
10. An electronic device comprising the electrochemical device according to any one of claims 1 to 9.
